Indonesian Case on Illegal Migrant - Ariadno, Melda Kamil (UI Scholars Hub, 2012)
Indonesia has faced the problem of illegal immigrants for a long time, especially with the rise of war in other countries or other forms of oppression against a party who then makes them leave the country with the hope to live in another country better off than where they originated. The issue of